Organizational culture determines the way to conduct and interact with one another in an organization. Cultural paradigm operates a unique style of operation within an organization that has different beliefs, values, customs, and symbols. Corporate cultur - Shamsudin, Shamnad (International Journal of Psychosocial Rehabilitation, 2020)
Organizational culture determines the way to conduct and interact with one another in an organization. Cultural paradigm operates a unique style of operation within an organization that has different beliefs, values, customs, and symbols. Corporate culture together provides a guide for employees and organizations. The biggest challenge for any organization at a time of change is to change its culture, because the employees are already committed to certain things. The purpose of this study is to understand how organizational culture affects the performance of its employees. And to describe the relationship between different cultures of organizational culture and employee performance studies. In this study the expressive research project was accepted Employees were selected to complete the study's questionnaire. The results of this study relate only to employees of the Technopark IT organization in Trivandrum. Based on the results, it was noted that the performance of the IT sector employee depends on various factors. They also find that there is general culture and different cultures, such as organizational culture, influence performance and positive influence. According to the results of tests obtained by employees in the organization. The company should take the organizational culture seriously and fix the performance of its employees.